2019
DOI: 10.1177/0192513x19859611
|View full text |Cite
|
Sign up to set email alerts
|

Impulse Control Moderates the Link Between Parent–Child Cultural Orientation Gaps and Externalizing Problems in Chinese Immigrant Early Adolescents

Abstract: The current study aimed to investigate whether the expected association between parent–child cultural orientation gaps and externalizing problems was moderated by impulse control (IC) among Chinese early adolescents in immigrant families. Ninety-one first- and second-generation Chinese immigrant youths (58% girls) aged between 11 and 13 years and their parents completed independent measures of mainstream and heritage cultural orientations. IC was evaluated via a computerized version of the Iowa Gambling Task, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Moreover, previous research suggested that parent–child gaps in cultural orientations can increase immigrant youth's risk for maladjustment by escalating parent–child conflict (Lui, 2015). In a study of early adolescents in Chinese‐Italian families, low impulse control was related to greater externalizing behavior in families with larger gaps in parent–child heritage cultural orientation (Miconi et al, 2019). Thus, we will examine whether parent–child cultural orientation gaps predict children's self‐regulatory skills longitudinally.…”
Section: Concepts Of Self‐regulation and Its Development In Sociocult...mentioning
confidence: 99%
“…Moreover, previous research suggested that parent–child gaps in cultural orientations can increase immigrant youth's risk for maladjustment by escalating parent–child conflict (Lui, 2015). In a study of early adolescents in Chinese‐Italian families, low impulse control was related to greater externalizing behavior in families with larger gaps in parent–child heritage cultural orientation (Miconi et al, 2019). Thus, we will examine whether parent–child cultural orientation gaps predict children's self‐regulatory skills longitudinally.…”
Section: Concepts Of Self‐regulation and Its Development In Sociocult...mentioning
confidence: 99%